A New Visual Stimulation Program for Improving Visual Acuity in Children with Visual Impairment: A Pilot Study - Tsai, Li-Ting; Hsu, Jung-Lung; Wu, Chien-Te; Chen, Chia-Ching; Su, Yu-Chin (Frontiers in Human Neuroscience, 2016)
The purpose of this study was to investigate the effectiveness of visual rehabilitation of a computer-based visual stimulation (VS) program combining checkerboard pattern reversal (passive stimulation) with oddball stimuli (attentional modulation) for improving the visual acuity (VA) of visually impaired (VI) children and children with amblyopia and additional developmental problems. Six children (3 females, 3 males; mean age = 3.9 ± 2.3 years) with impaired VA caused by deficits along the anterior and/or posterior visual pathways were recruited. Participants received eight rounds of VS training (two rounds per week) of at least 8 sessions per round. Each session consisted of stimulation with 200 or 300 pattern reversals. Assessments of VA (assessed with the Lea symbol VA test or Teller VA cards), visual evoked potential (VEP), and functional vision (assessed with the Chinese-version Functional Vision Questionnaire, FVQ) were carried out before and after the VS program. Significant gains in VA were found after the VS training (VA=1.05 logMAR ± 0.80 to 0.61 logMAR ± 0.53, Z=-2.20, asymptotic significance (2-tailed) =0.028). No significant changes were observed in the FVQ assessment (92.8 ± 12.6 to 100.8 ± SD=15.4, Z=-1.46, asymptotic significance (2-tailed) = 0.144). VEP measurement showed improvement in P100 latency and amplitude or integration of the waveform in two participants. Our results indicate that a computer-based VS program with passive checkerboard stimulation, oddball stimulus design, and interesting auditory feedback could be considered as a potential intervention option to improve the VA of a wide age range of VI children and children with impaired VA combined with other neurological disorders.